First order differential subordination associated with cassini curve - Andy Liew Pik Hern; Rashidah Omar; Aini Janteng (2020)
Let p be an analytic function defined on the open unit disc with p01. In this paper, we determine the conditions for such that certain subordination properties hold for p z is subjected to certain geometric conditions involving the expressions 1 ' , zp z1 ' /zp z p z and 2 1 ' / zp z p z of which each is subordinated to 1cz and the condition for is determined.